Lesbian coaches: Personal perspectives on being out - Cohen, Elissa (University of Ottawa (Canada), 2009)
This research project attempted to identify and describe the essence of the experience of being an out lesbian in elite coaching. Through the use of a feminist epistemology, a phenomenological methodology, and in-depth interviews with eight high performance coaches who identify as lesbian, it was possible to identify and describe the essence of their experiences being out lesbians in elite coaching. The data were analyzed using an inductive phenomenological analysis procedure. The six themes that emerged from the data were: sexism, lesbophobia, the old boys' club, acknowledgement and positive reinforcement, the supportive feminist network, and the nature of the job. Sport was identified as a domain rife with sexism, lesbophobia, and dominated by the old boys' club all of which negatively impacted the lesbian coaches' experiences and career advancement. However, with positive reinforcement of their lesbian identity and the supportive feminist network, the participants nevertheless experienced great personal and professional success.
Keywords: GLBT Studies.; Health Sciences, Recreation.